Influence of the Capping on the Atomistic Arrangement in Palladium Nanoparticles at Room Temperature - Corthey, Gastón (2014)
The role that protecting molecules have on the way that palladium atoms arrange themselves in nanoparticles prepared at room temperature was studied by the analysis of aberration-corrected scanning transmission electron microscopy images and atomistic Langevin dynamics simulations. It was found that the arrangement of Pd atoms is less ordered in thiolate-protected nanoparticles than in amine-protected ones. The experimental and theoretical data showed that the disorder in ∼3 nm thiolate-protected particles is promoted by the strong S−Pd bond in the sulfide layer that surrounds the nanoparticles.